Hubungan Hubungan Komponen Health Belief Model dengan Perilaku Penerapan Protokol Kesehatan COVID-19 di RW 12 Kelurahan Bendul Merisi Surabaya - Fikri Hanif (Universitas Airlangga, 2023)
Background: The outbreak of the Covid 19 virus worldwide has caused many victims to fall, as well as residents of the Bendul Merisi sub-district who have been hit by 928 cases. The case was recorded as the area with the highest cases in Surabaya. This bad record is due to the habits of its citizens who do not comply with the COVID-19 health protocol. Objectives: To analyze the factors from the Health Belief Model with the behavior of implementing the COVID-19 health protocol. Methods: This research has used a cross-sectional method on the population of RW 12 Kelurahan Bendul Merisi Surabaya with a population of 6,125 and the use of the Lemeshow sampling method with a 95% confidence level has resulted in a sample of 191 people using a questionnaire instrument through the Google form. Results: This research has resulted in a weak relationship between perceived vulnerability, perceived severity, perceived obstacles and perceived threats to the behavior of implementing the COVID-19 health protocol and a strong relationship between cues to take action on the behavior of implementing the COVID-19 health protocol. Conclusions: This research has concluded that there is a significant correlation between factors from the theory of the Health Belief Model on health protocols in the era of the COVID-19 pandemic in residents of RW 12 Bendul Merisi Village, Surabaya.